Postoperative Disposal of Unused Opioids: A Systematic Review. Issue 2 (July 2021) - Lamplot, Joseph D.; Premkumar, Ajay; James, Evan W.; Lawton, Cort D.; Pearle, Andrew D.
Introduction : Opioid misuse and overprescription have contributed to a national public health crisis in the United States. Postoperatively, patients are often left with unused opioids, which pose a risk for diversion if not appropriately disposed of. Patients are infrequently provided instructions on safe disposal methods of surplus opioids. Purpose : We sought to determine the current rates of disposal of unused opioids and the reported disposal mechanisms for unused opioids that were prescribed for acute postoperative pain control. Methods : A systematic review was performed of the PubMed, Cochrane, and Embase databases for relevant articles from their earliest entries through October 2, 2019. We used the search terms "opioid" or "narcotic" and "disposal" and "surgery." Studies were considered for inclusion if they reported the rate of disposal of unused opioids following surgery. A screening strategy was used to identify relevant articles using Covidence. For studies meeting inclusion criteria, relevant information was extracted. Results : Sixteen studies met inclusion criteria. We found that surplus opioid disposal rates varied widely, from 4.9% to 87.0%. Among studies with no intervention (opioid disposal education or drug disposal kit/bag), rates of opioid disposal ranged from 4.9% to 46.5%. While 7 studies used opioid disposal education as an intervention, only 3 showed a significant increase in surplus opioid disposal compared with standard care. All 3 studies that used an opioid disposal kit or bag as an intervention demonstrated significant increases in opioid disposal. Conclusions : Baseline rates of surplus opioid disposal are relatively low in the postoperative setting. Our findings suggest that opioid disposal kits significantly increase rates of surplus opioid disposal postoperatively. Further research, including a large-scale cost-benefit analysis, will be necessary prior to recommending widespread implementation of drug disposal kits or bags.